How does patent litigation influence dynamic risk for market competitors? - Wang, Yi-Hsien; Lin, Wan-Rung; Lin, Shu-Shian; Hung, Jui-Cheng (Technological and Economic Development of Economy, 2017)
Many recent studies have discussed the appropriateness of various patent measurement indicators, as well as the differences in the positioning of patented technologies, while there is little discussion on the risk transmission of enterprises when faced with infringement litigation. This study used the bivariate EGARCH (Exponential Generalized Autoregressive Conditional Heteroskedasticity) model with DCC (Dynamic Conditional Correlations) to investigate the dynamic risk transmission of patent litigation between market competitors in the smartphone industry. Empirical results revealed that when facing lawsuits from market challengers, the market leader faces fewer risks when handling patent infringement litigations. In addition, the risk reactions of competitors during patent wars may widely differ. Investors should consider the patent infringement litigations when measuring the dynamic risks of share prices, and determining the optimal configuration of asset portfolios in response.First published online: 03 Nov 2015